Interaction Between Langmuir Films Of Calix[4]Arenes With Aqueous Lead Ions - Azahari Noor Azyyati, Supian Faridah Lisa, Malik Syed Abdul, (N/A, 2012)
Interaction Between Langmuir Films Of Calix[4]Arenes With Aqueous Lead Ions by Azahari Noor Azyyati, Supian Faridah Lisa, Malik Syed Abdul,